Names we gave the North Star - Stopher, Aliceanna, author; Doenges, Judy, advisor; Candelaria Fletcher, Harrison, committee member; Vasudevan, Ramaa, committee member (Colorado State University. Libraries, 2019)
This thesis is interested in names. This thesis is interested in girls and women. This thesis is interested in kin. This thesis is interested in divination, in lightness, in knowing. This thesis is interested in memory–its inexactness, its gaps, in the push-pull between truth and speculation, in how much that may or may not matter. This thesis is interested in hybridity. The stories and essays in this collection seek to blur between true and untrue as a reflection of memory as constellation of facts, conjecture, and dreams. Find here mountains that are and are not my mountains, homes that are and are not my homes. Know there is a presence, my presence, on the other side of each page. Come closer. Press your palm against each page, feel the warmth of mine from the other side. Make yourself at home here.